2020
DOI: 10.1002/eap.2245
|View full text |Cite
|
Sign up to set email alerts
|

Continental‐scale dynamics of avian influenza in U.S. waterfowl are driven by demography, migration, and temperature

Abstract: Emerging diseases of wildlife origin are increasingly spilling over into humans and domestic animals. Surveillance and risk assessments for transmission between these populations are informed by a mechanistic understanding of the pathogens in wildlife reservoirs. For avian influenza viruses (AIV), much observational and experimental work in wildlife has been conducted at local scales, yet fully understanding their spread and distribution requires assessing the mechanisms acting at both local, (e.g., intrinsic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 59 publications
4
10
0
Order By: Relevance
“…This information is also useful in helping to inform management practices aiming to mitigate IAV outbreaks in the United States. Specifically, we confirmed the highest IAV prevalence in many dabbling duck species in the autumn, consistent with prior research 15 , 18 20 . We also elucidate broad temporal trends in prevalence.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This information is also useful in helping to inform management practices aiming to mitigate IAV outbreaks in the United States. Specifically, we confirmed the highest IAV prevalence in many dabbling duck species in the autumn, consistent with prior research 15 , 18 20 . We also elucidate broad temporal trends in prevalence.…”
Section: Discussionsupporting
confidence: 91%
“…We found seasonal variation both among and within species. Overall, most species showed an increase in IAV prevalence in the autumn, a pattern that is well established and consistent with past work 15 , 18 20 . This pattern is presumably caused by high infection rates among recently fledged, immune-naïve juvenile birds entering the population in late summer and fall 8 , 26 .…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with other broad‐scale evaluations of IAVs in waterfowl in North America (Bevins et al., 2014; Gorsich et al., 2020), we identified variability in infection prevalence across years, sampling month and flyways. However, the correlations identified by our regression model should be interpreted with some caution because the interagency surveillance programme necessarily had a somewhat unbalanced sampling design, partially due to a reliance on opportunistic sampling (e.g.…”
Section: Discussionsupporting
confidence: 89%
“…The peak median response occurred on 10 dpi and was followed by a gradual decline Because antibody levels for exposed birds dropped below detectable limits by six months post-exposure for most individuals, it is possible that our initial pre-screen may not have identified a prior exposure since the birds were approximately a year old when we acquired them. However, in the event of a previous exposure, we would have expected to see an anamnestic response (a rapid rise in antibodies against a previously encountered pathogen recognized by memory cells), but ELISA results for days 2 and 4 post-inoculation did Consistent with other broad-scale evaluations of IAVs in waterfowl in North America (Bevins et al, 2014;Gorsich et al, 2020), we identified variability in infection prevalence across years, sampling month and flyways. However, the correlations identified by our regression model should be interpreted with some caution because the interagency surveillance programme necessarily had a somewhat unbalanced sampling design, partially due to a reliance on opportunistic sampling (e.g.…”
Section: Long-term Antibody Kineticssupporting
confidence: 77%
“…LPAI viruses have been identified in a wide range of other birds and mammals, including felines, canines, suids, equines, and mustelids [95][96][97]. The local spread and evolution of LPAI viruses can lead to continental-scale distribution [98]. One LPAI currently circulating worldwide is H9N2, which poses a great risk to small scale and family farms, where it may have great socioeconomic effects [94,[99][100][101].…”
Section: Avian Influenzamentioning
confidence: 99%